Construction of the mathematical model of the strength of post-consumer wood made blockboard of different designs - Serhiy Gayda; Lyubomyr Medvid (Наукові праці Лісівничої академії наук України)
It is substantiated that any wood resources should be used rationally and comprehensively, in particular this applies to wood residues from various stages of primary wood processing – from logging to the creation of finished products. Secondly, according to the principles of the circular economy, the issue of processing post-consumer wood (PCW) as an additional resource of wood, which has already lost its consumer characteristics in products, and which, with proper processing, minimizes the negative impact on the environment, has become more relevant than ever. Thirdly, this partially solves the problems related to the increase of wood residues and waste, the accumulation of used wood in landfills, as well as environmental problems. A batch of pine PCW-made blockboards was prepared by implementing a second-order B-plan, where the variables were the width of the strips of tangential and radial sawing. The strength limit during static bending for pine PCW-made blockboard was determined experimentally and an adequate mathematical (regression) model was constructed depending on the alternate laying of radial (Вrad) and tangential (Вtan) strips with widths of 32, 52 and 72 mm. It was found that the width of the strips in blockboard structures with 22 mm thick PCW significantly affects the strength characteristics of the blockboard cores. It was found that an increase in width from 32 to 72 mm during the determination of the strength limit in static bending leads to a decrease in the indicator for radial strips by 13.29-16.70%, and for tangential strips by 24.83-27.79%. It was established that the strength limit during static bending of all pine PCW-made blockboards, regardless of their design, meets the regulatory requirements. According to the results of experimental studies, it was established that the maximum value of the strength limit during static bending σu = 39.199 MPa can be obtained by fixing the dimensions of the widths of the strips of pine PCW-made blockboard of combined laying at the level: Brad (x1) = 32 mm, Btan (x2) = 32 mm. Based on practical experience, it is recommended to use post-consumer wood (PCW) for the production of blockboards with a cross-section of strips in a ratio of no more than 1:5 in the case of combined radial and tangential laying, and in case of random laying – in a ratio of no more than 1:3. Practical recommendations for the production of PCW-made blockboard have been developed: moisture content of strips – 8±2%; for rails: the width should be 3-5 times the thickness; arrangement of strips – radial or at an angle of more than 45o; facing – 3 mm thick plywood; consumption of glue for the blockboard core – 200-250 g/m2; glue consumption for the blockboard facing – 150-200 g/m2; the temperature of the clamp for the blockboard core is 85-90 ºС; the temperature of the press for PCW-made blockboard – 115-125 ºС; the exposure time under pressure for the blockboard core is 30-40 minutes; holding time under pressure for PCW-made blockboard – 4-6 minutes; pressure for blockboard core – 0.5-1.0 MPa; for PCW-made blockboard – 1.2-1.3 MPa . Sorted and sawn to the appropriate cross-sectional dimensions, strips made from PCW of various species can be used to manufacture glued panel elements, in particular, blockboards and furniture panels. Therefore, the development of practical recommendations is certainly the basis for the rapid introduction of PCW into production processes.